2015
DOI: 10.1055/s-0035-1553428
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent D-dimer Cut-off to Avoid Unnecessary CT-Exams for Ruling-out Pulmonary Embolism

Abstract: Purpose: To evaluate the effect of an age-dependent D-Dimer cut-off in patients who underwent a computed tomography pulmonary angiogram (CTPA) for suspected pulmonary embolism (PE) Material and Methods: Retrospective application of an age-dependent D-dimer cut-off (age/100 in patients aged over 50) in 530 consecutive patients, both in- and outpatients, aged over 18, who underwent CTPA for suspected PE according to the guidelines. Results: The application of an age-dependent D-dimer cut-off showed a now negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(23 reference statements)
1
5
0
1
Order By: Relevance
“…This high prevalence of CTPA ordered on otherwise low-risk patients is not unique to our site, and has in fact been reported in similar rates in other studies [30,31]. It should be noted that our results did show a slightly higher proportion of clinically significant pulmonary emboli (2.9%) among D-Dimer negative patients than has been found in previous similar studies [8,[30][31][32][33][34][35]. This slight discrepancy may be due to the different D-Dimer assays used in the different studies, or sample sizes too small in those studies to capture D-Dimer false negative patients, a higher prevalence in our study of patients with chronic PE or already on anticoagulants, or variability and discordance among radiologists in their interpretations of CTPAs and diagnosis of pulmonary embolism [12,36].…”
Section: Discussionsupporting
confidence: 89%
“…This high prevalence of CTPA ordered on otherwise low-risk patients is not unique to our site, and has in fact been reported in similar rates in other studies [30,31]. It should be noted that our results did show a slightly higher proportion of clinically significant pulmonary emboli (2.9%) among D-Dimer negative patients than has been found in previous similar studies [8,[30][31][32][33][34][35]. This slight discrepancy may be due to the different D-Dimer assays used in the different studies, or sample sizes too small in those studies to capture D-Dimer false negative patients, a higher prevalence in our study of patients with chronic PE or already on anticoagulants, or variability and discordance among radiologists in their interpretations of CTPAs and diagnosis of pulmonary embolism [12,36].…”
Section: Discussionsupporting
confidence: 89%
“…However, its clinical usage is limited due to high false‐negative rate. 26 , 27 , 28 , 29 , 30 , 31 The results of our study showed that SCUBE‐1 is less sensitive than D‐dimmer in the diagnosis of PE, but it has great advantages in specificity. Therefore, it may be considered as a first‐line screening tool to rule out the false PE risk.…”
Section: Discussionmentioning
confidence: 70%
“…D‐dimer is a product of the fibrinolysis process, and coagulation activation is recommended as an initial test in all PE guidelines. However, its clinical usage is limited due to high false‐negative rate 26–31 . The results of our study showed that SCUBE‐1 is less sensitive than D‐dimmer in the diagnosis of PE, but it has great advantages in specificity.…”
Section: Discussionmentioning
confidence: 79%
“…This result is consistent with the findings of other similar studies. Table 3 summarizes the results of five studies, [19][20][21][22][23] which documented decreases ranging from 8.7% 22 to 20.1%, 19 consistently showing an increase in the negative predictive value at the expense of a slight reduction in specificity. 20,22,23 The effect is more relevant among those over 80 years of age 20 and appears to be useful in both hospital and outpatient settings.…”
Section: Discussionmentioning
confidence: 99%